Replacement of concentrate with three species of tree forages ( Artocarpus heterophyllus, Gliricidia sepium and Leuceana leucocephala) on the performance of crossbred dorper sheep fed napier silage based feed - Kelana, Muhammad Fajrul (2017)
The aim of this study is to determine the effects of using multiple species forage which are Jackfruit (Artocarpus heterophyllus), Glirisidia (Gliricidia sepium) and Leuceana (Leuceana leucocephala) as sheep feeds. In addition, evaluate the average daily gain (ADG), bodyweight gain, digestibility and dry matter intake of sheep. The digestibility analysis conducted by using in vitro gas-production. Proximate analysis was conducted at Nutritional laboratory, Department of Animal Science, Faculty, UPM. Twelve female crossbred Dorper sheep are raised in intensive system. Mineral block and clean drinking water were provided ad libitum. Four treatment diets were formulated in which containing 70% Napier grass silage +30% pellets as T1, 70% Napier grass silage + 10% Tree Forage mixture (Jackfruit, Glirisidia and Leuceana) + 20% pellets as T2, 70% Napier grass silage+ 20% Tree Forage mixture (Jackfruit, Glirisidia and Leuceana) + 10 % pellets as T3, 70% Napier grass silage + 30% Tree Forage mixture (Jackfruit, Glirisidia and Leuceana) as T4. The experimental design was a Complete Randomized Design. 1000 kg of Napier grass is harvested and prepare for silage making and addition of molasses by using 5% of silage weight. Furthermore, 12 female Dorper sheep are rear at growing stage under intensive system by grouping pens. Sheeps were allocated into four dietary treatments with three sheep in each group. The feeding trial for sheep is carried out with different percentage of pellet and three species of tree forages (based on the treatment) with 3 replicates.The diets given were 3% of bodyweight of the sheep. The parameters recorded in this experiment is the determination of nutritive value of the feeds and weekly bodyweight gain of sheeps. During the feeding trial, the average daily gain (ADG), average dry matter feed intake and digestibility also will be taken into consideration. Thus, one-way analysis of variance (ANOVA) will be carried for the experimental data by using Statistical Analysis Software (SAS). The bodyweight gain, average daily gain and average dry matter intake were determined by each treatment within period for 6 week. There was no significant (p>0.05) differences of bodyweight gain and average dry matter intake between all treatment and also between period. However, treatment 1 which is served as control is significant (p>0.05) with treatment 2, 3 and 4. In contrast, the average daily gain (ADG) of the sheep on week 1 until week 3 shows the significant difference (p>0.05). The feeds were analysed for chemical composition and digestibility. Generally, nutrient digestibility for treatment 2 was highest compared to other treatment. Eventhough the gas production was high, there was no significant (p>0.05) different of nutrient digestibility on different treatment. In conclusion, the three species of tree forages (Jackfruit, Glirisidia and Leuceana) can replaced partially of concentrate as a feed resource for the sheeps.